A Bionanozyme with Ultrahigh Activity Enables Spatiotemporally Controlled Reactive Oxygen Species Generation for Cancer Therapy. (14th July 2021) - Xu, Zhen; Zhang, Li; Pan, Min; Jiang, Qunying; Huang, Yunjie; Wang, Fuan; Liu, Xiaoqing
Abstract: Nanozymes hold great potential in nanomedicine, yet biotoxicity limits their clinical translation because of their uncontrolled catalytic activity, artificial inorganic components, and harsh synthesis conditions. Herein, a peroxidase‐like bionanozyme with ultrahigh and photocontrolled catalytic activity through the self‐assembly of biomolecules, hemin, and in situ polymerization of pyrrole in an aqueous solution is reported. Such bionanozymes leverage the specific cues of the tumor microenvironment and precise light‐induced photothermal heating for spatiotemporally controlled reactive oxygen species generation in tumors. The tunable catalytic activity and excellent biocompatibility of the bionanozyme result in high cancer cell apoptosis and tumor growth inhibition in murine models with negligible biotoxicity. This work highlights the potential of biomolecule‐based nanozymes for cancer‐specific therapy. Bionanozymes with ultrahigh and tunable catalytic activity may lay the important foundation for more advanced nanomedicine and biosensing. Abstract : A biomolecule‐based nanozyme leverages the specific cues of the tumor microenvironment and precise light‐induced photothermal heating for spatiotemporally controlled reactive oxygen species generation in tumors. This strategy provides insight into constructing catalytic nanomaterials with excellent biocompatibility for precision nanomedicine.